2015
DOI: 10.1124/jpet.115.224485
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Liver X Receptor Has Potent Anti-HIV Effects in a Humanized Mouse Model of HIV Infection

Abstract: Previous studies demonstrated that liver X receptor (LXR) agonists inhibit human immunodeficiency virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…7B b ), consistent with demonstrated rescue by the compound of Nef-inhibited cholesterol efflux (Fig. 7A) and previous studies demonstrating anti-HIV activity of ABCA1 and ABCA1-stimulated cholesterol efflux 28, 35, 36 . Consistent with previous studies 1, 5, 36 , cholesterol efflux from HIV-infected cells was decreased by 60%, whereas HIV-infected cells treated with NSC 13987 showed cholesterol efflux not significantly different from that of mock-infected cells (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…7B b ), consistent with demonstrated rescue by the compound of Nef-inhibited cholesterol efflux (Fig. 7A) and previous studies demonstrating anti-HIV activity of ABCA1 and ABCA1-stimulated cholesterol efflux 28, 35, 36 . Consistent with previous studies 1, 5, 36 , cholesterol efflux from HIV-infected cells was decreased by 60%, whereas HIV-infected cells treated with NSC 13987 showed cholesterol efflux not significantly different from that of mock-infected cells (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Our previous studies demonstrated that HIV critically depends on interaction with host cholesterol metabolism and modifies it for optimization of viral replication 1, 2, 28, 35, 36 . Specifically, HIV, through viral protein Nef, reduces abundance and impairs functional activity of ABCA1, a key transporter in cholesterol efflux pathway 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDV infection disturbs the lipid metabolism in chickens [32]. Studies on various viruses demonstrate that the pharmacological agents targeting lipid metabolism can inhibit virus infection [30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, agonists of Liver X Receptors under development as a cardiovascular drug, were potentially active in supressing HIV and prion infection. 6,39 Infectious origin of cardiovascular diseases was once a popular hypothesis 40 and involvement of HCMV in pathogenesis of atherosclerosis was suspected for a long time. 41 Perhaps the last word on connection between infection and cardiovascular and metabolic diseases is yet to be said.…”
mentioning
confidence: 99%